Implementasi E-Learning dalam Pembelajaran Bahasa Arab Era COVID-19 di SMP Muhammadiyah 5 Tulangan - Nuriyah, Lilik; Hikmah, Khizanatul (Indonesian Journal Publisher, 2023)
Learning in the early days of COVID-19 with teaching and learning orders at home, the majority of schools used E-Learning, including Arabic language learning. This study aims to determine the implementation of E-learning in Arabic learning in the Covid-19 Era at SMP Muhammadiyah 5 Tulangan, and find out the supporting and inhibiting factors of the implementation of E-learning. Researchers use descriptive qualitative research methods. Researchers use data collection techniques through interviews, observations, and documentation. The data analysis used is data reduction, data presentation, and conclusion drawing. The results of the research obtained are (1) The implementation of E-learning used in learning Arabic in the Era of COVID-19 at SMP Muhammadiyah 5 Tulangan is Internet Based. The applications used are WhatsApp, google classroom, google meet, zoom meeting, and Youtube. With the planning made by the teaching teacher himself in accordance with the implementation used through the application above and evaluation in the form of question exercises, (2) The inhibiting factors are infrastructure, teachers cannot measure the level of understanding of students, and the instability of the internet. While the supporting factor is the existence of Youtube media, Zoom meetings or the like.